Foreign blood, local heart. - Foo, Chee Chang. (2011)
Foreign Blood, Local Heart is a book project that presents a look at the multifarious nature of immigration in Singapore, and contains a selection of stories of individuals who have decided to call Singapore home - by becoming citizens. Each of the 26 profiles explores the background and motivations of each individual in their road to becoming Singaporean. Accompanying each profile are 2 thoughtfully constructed photographs – a headshot and an environmental portrait. Together, they seek to put a very human face on an issue that is more often than not expressed in terms of figures and charts.